Ակնարկ հայկական արձանագրութեամբ կամ հայապատկան կնիք կրող պղնձեայ դգալներու եւ պատառաքաղներու - Տագէսեան, Անդրանիկ (տպ. Atlas)
The study focuses on the diverse forms of copper forks and spoons, which have Armenian inscriptions or have Armenian names inscribed in Arabic or Latin letters. Unlike copper bath tasses, tasses used for clay, plates, or divits, the forks and spoons are molded rather than hammered and shaped by hand. And unlike the abovementioned utensils, none of these have any dates or any data that hint at their provenance. The author notes that no knives with such inscriptions have been found yet, though surely the craftsmen produced knives as well. Basing his analysis on an extensive collection of forks and spoons that belong to three antique collectors, the author has been able to discern 29 different inscriptions, of which 21 are found on the spoons, 6 on the forks and 2 on rounded spoons (used by chemists for measurement). Certain inscriptions are found both on spoons and forks as well.
Keywords: Արուեստ; Պղնձագործութիւն